Role of Aldo–Keto Reductase Enzymes in Mediating the Timing of Parturition - Byrns, Michael C. (Frontiers in Pharmacology, 2012)
A better understanding of the mechanisms underlying the initiation of parturition would provide an important step towards the development of more effective therapies for the prevention of pre-term labor and the associated neonatal morbidity and mortality. Expression of aldo-keto reductases (AKR) from the 1D, 1C, and 1B subfamilies are likely to play an important role in determining the timing of parturition through their effects on metabolism of progesterone and prostaglandins. Placental expression of AKR1D1 (human 5β reductase) likely contributes to the maintenance of pregnancy by inhibiting myometrial contractility through the formation of 5β-dihydroprogesterone (DHP). AKR1C1, AKR1C2, and AKR1C3 all catalyze the 20-ketosteroid reduction of progestins and can also catalyze the 3-ketosteroid reduction of pregnanes. They could therefore be playing an important role in eliminating tocolytic progestins at term. Activation of the F prostanoid receptor by its ligands also plays a critical role in initiation of labor. AKR1C3 also has prostaglandin (PG) F synthase activities that would contribute to the initiation of labor. AKR1C3 converts PGH2 to PGF2α and PGD2 to 9α,11β-PGF2. AKR1B1 also contributes to the conversion of PGH2 to PGF2α, but does not form 9α,11β-PGF2. Consistent with the potential role for AKR1C3 in the initiation of parturition, indomethacin, which is a potent and isoform selective inhibitor of AKR1C3, has long been used for tocolysis.